2019
DOI: 10.1130/g45852.1
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircons reveal sea-level and hydroclimate controls on Amazon River to deep-sea fan sediment transfer

Abstract: We use new U-Pb detrital zircon (DZ) geochronology from the Pleistocene Amazon submarine fan (n = 1352 grains), integrated with onshore DZ age data, to propose a sedimentary model for sea level-modulated and hydroclimate-modulated sediment transfer in Earth's largest source-to-sink system. DZ ages from the modern Amazon River sediment display a progressive downstream dilution by older cratonic zircons, leading to the expectation of a submarine fan with high proportions of craton-derived sediment. Our new DZ ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…Submarine canyon–channel‐fan systems are important for transferring sediment and other materials (for example, organic carbon, microplastics and other pollutants) from terrestrial to deep marine environments (Normark et al ., 1993; Hessler & Fildani, 2019; Kane et al ., 2020; Pohl et al ., 2020). Their sedimentary deposits store a wealth of information about the Earth’s history (for example, climate and tectonic events, Clift, 2006; Castelltort et al ., 2017; Daniels et al ., 2018; Fildani et al ., 2018; Mason et al ., 2019), provide a long‐term record of turbidity current events required for seafloor hazard assessments (e.g. Goldfinger, 2011; Clare et al ., 2015, 2016; Jobe et al ., 2018) and host significant natural resources (for example, hydrocarbons, Pettingill & Weimer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Submarine canyon–channel‐fan systems are important for transferring sediment and other materials (for example, organic carbon, microplastics and other pollutants) from terrestrial to deep marine environments (Normark et al ., 1993; Hessler & Fildani, 2019; Kane et al ., 2020; Pohl et al ., 2020). Their sedimentary deposits store a wealth of information about the Earth’s history (for example, climate and tectonic events, Clift, 2006; Castelltort et al ., 2017; Daniels et al ., 2018; Fildani et al ., 2018; Mason et al ., 2019), provide a long‐term record of turbidity current events required for seafloor hazard assessments (e.g. Goldfinger, 2011; Clare et al ., 2015, 2016; Jobe et al ., 2018) and host significant natural resources (for example, hydrocarbons, Pettingill & Weimer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Harris and Mix (2002) showed that up to 8 Ma (except for the interval 12 to 10 Ma) precipitation rates were relatively high, followed by a shift to drier conditions from 8 Ma. The transition from Neogene to Quaternary coincided with the rise of Poaceae pollen, as observed in the Amazon submarine fan record (Hoorn et al 2017), and also with a general increase in terrigenous Andean sediment (Lammertsma et al 2018;Mason et al, 2019). The further decline in the ratio of oxide minerals from 4.5 Ma, indicative of aridification, is paralleled by a rise in Poaceae and the introduction of high Andean taxa.…”
Section: Global Climate As Indirect Driver Of Vegetation Dynamicsmentioning
confidence: 75%
“…The sediments show a predominance of Mesoproterozoic detrital U/Pb zircon ages, with relatively few Archean grains (e.g., Cawood & Nemchin, 2000), suggesting that despite its close proximity, the extensive Yilgarn Craton was not an important provenance for basin fill. Furthermore, recent detrital records of river systems and coastal deposits adjacent to shields do not contain the expected significant zircon populations given their close location to exposed cratonic areas (e.g., Western Australia Quaternary coastal deposits, Sircombe & Freeman, 1999; Mississippi River, Blum et al, 2017; Amazon River, Mason et al, 2019). One explanation for this lack of detrital contribution from cratons is that their peneplanation was complete before the Quaternary and that denudation rates have been minimal since that time (Sircombe & Freeman, 1999).…”
Section: Discussionmentioning
confidence: 99%